2022
DOI: 10.15430/jcp.2022.27.2.129
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Clinical Study to Investigate the Hypomethylating Properties of Freeze-dried Black Raspberries in Patients with Myelodysplastic Syndrome or Myeloproliferative Neoplasm

Abstract: Myelodysplastic syndromes (MDS) and myelodysplastic/myeloproliferative neoplasms (MDS/MPN) are bone marrow disorders characterized by cytopenias and progression to acute myeloid leukemia. Hypomethylating agents (HMAs) are Food and Drug Administration-approved therapies for MDS and MDS/MPN patients. HMAs have improved patients' survival and quality of life when compared with other therapies. Although HMAs are effective in MDS and MDS/MPN patients, they are associated with significant toxicities that place a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study demonstrated that the supplementation of diet with 5% BRBs in Vav-cre Asxl1 fl/fl Tet2 fl/fl mice has distinct effects on hematopoietic pathways potentially related to the development of MDS. Our pilot clinical study illustrated the hypomethylating effects of BRBs in individuals diagnosed with myelodysplastic syndrome or myeloproliferative neoplasm [ 8 ]. Pathway analysis indicates that the intragenic hypomethylation induced by BRBs plays a role in prompting leukocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that the supplementation of diet with 5% BRBs in Vav-cre Asxl1 fl/fl Tet2 fl/fl mice has distinct effects on hematopoietic pathways potentially related to the development of MDS. Our pilot clinical study illustrated the hypomethylating effects of BRBs in individuals diagnosed with myelodysplastic syndrome or myeloproliferative neoplasm [ 8 ]. Pathway analysis indicates that the intragenic hypomethylation induced by BRBs plays a role in prompting leukocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4 TSS and intragenic_hyper-and hypo-methylation old wild-type (n = 6) and Vav-cre Asxl1 fl/fl Tet2 fl/fl (n = 10) mice were fed 5% BRBs for 12 weeks. The circulating blood was used for the Wright-Giemsa stain, and CD45 + cells from circulating blood were used for the Reduced Representation Bisulfite Sequencing (RRBS) assay; data analysis was performed as described [8]. A modified software based on Metilene and Wilcoxon Signed Rank Test was applied to identify the differentially methylated region (DMR) de novo among samples.…”
Section: Methodsmentioning
confidence: 99%
“…These observations were attributed to both a hypomethylation of intergenic regions and a hypermethylation of intragenic and intergenic regions. These effects also manifested without significant side effects or adverse effects in study patients which demonstrates the desired safety profile of BRB intervention [ 97 ]. The precise impact of the observed hypermethylation events will require further investigation.…”
Section: Black Raspberries and Other Diseasesmentioning
confidence: 99%
“…Myelodysplastic syndrome (MDS) is a heterogeneous group of clonal diseases originating from hematopoietic myeloid-directed stem cells or pluripotent stem cells, and about 10% of patients with MDS may develop secondary to autoimmune diseases ( Dong et al, 2022 ). It has been shown that some patients with MDS have a higher probability of secondary autoimmune disease than their natural incidence, while others have no clinical manifestations of immune disease but may have abnormal immunologic parameters, providing further evidence of the association between MDS and autoimmune disease ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%